Environmental factors that associated adults' participation in physical activity at residential area Taman Temerloh Jaya Pahang / Mohd Musthakim Che Man - Che Man, Mohd Musthakim (2015)
Promoting physical activity is a public health priority, and changes in the environmental contexts of adults' activity choices are believed to be crucial. However, of the factors associated with physical activity, environmental influences are among the least understood. Assessment of physical activity need to be improve in order to gain more comprehensive understanding of the relationship between characteristics of the environment and physical activity. These research aims are to study the environmental factor that influences adults' participation in physical activity at residential area at Taman Temerloh Jaya, Pahang. This research is based on data obtained from a survey questionnaire that polled public perceptions regarding the factor of physical environment. The data was analysed to identify the relationship between demographic variables and environmental factors that associated adults' participation in physical activity. The results of the study also suggested that strategic approach in order to influences the adults' population to participate in physical activity. It is hope that the study can contribute in promoting physical activity at residential area at Taman Temerloh Jaya, Pahang. The findings of this study show the significant relationship in gender, race, educational backgrounds and residential areas towards environmental factors that associated adults' participation in physical activity.